2022
DOI: 10.1128/iai.00522-21
|View full text |Cite
|
Sign up to set email alerts
|

Surveying the Epigenetic Landscape of Tuberculosis in Alveolar Macrophages

Abstract: Tuberculosis (TB) remains the leading cause of bacterial disease-related death and is among the top 10 overall causes of death worldwide. The complex nature of this infectious lung disease has proven difficult to treat, and significant research efforts are now evaluating the feasibility of host-directed, adjunctive therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 121 publications
1
6
0
Order By: Relevance
“…Further analysis of the 3D structure of DNA could be investigated using HiChIP. It is also important to note that this study was conducted exclusively with THP-1 macrophages, and while many identified signatures were consistent with literature from primary human monocyte derived macrophages, it would be prudent to confirm key findings in primary human macrophages, including alveolar macrophages, which are the most clinically relevant model for Mtb infection (Madden et al . 2022).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Further analysis of the 3D structure of DNA could be investigated using HiChIP. It is also important to note that this study was conducted exclusively with THP-1 macrophages, and while many identified signatures were consistent with literature from primary human monocyte derived macrophages, it would be prudent to confirm key findings in primary human macrophages, including alveolar macrophages, which are the most clinically relevant model for Mtb infection (Madden et al . 2022).…”
Section: Discussionsupporting
confidence: 72%
“…The only previous report to investigate global chromatin accessibility patterns in macrophages upon Mtb infection was a report by Correa-Macedo et al conducted in the context of HIV co-infection, which did not focus in-depth on the effects of Mtb infection alone (Correa-Macedo et al 2021). In contrast, numerous studies have examined the impact of Mtb infection on the transcriptome of macrophages (Madden et al 2022). These studies have shown a host-detrimental type I interferon (IFN) signature in Mtb infected cells and TB patients (Moreira-Teixeira et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a distinct DNA methylation profile, which was enriched in the pentose phosphate pathway, T cell migration and IFN‐γ production pathways, was uncovered in alveolar macrophages (AMs) after M. tuberculosis infection [39]. Intriguingly, there were more differentially methylated regions in AMs than in PMBCs within the same individual [38]. In addition, altered DNA methylation pattern associated with the immune gene loci can also be detected in the sperm DNA of parental male mice infected with fungus C. albicans [40].…”
Section: Trained Immunity (Innate Immunological Memory)mentioning
confidence: 99%
“…Additionally, gene ontology analysis revealed that promoters with altered DNA methylation patterns were strongly enriched among immune-related genes, thereby enhancing the resistance of macrophages to mycobacteria [35,36]. Indeed, a global methylation analysis showed that there existed over 1000 differentially methylated regions between PBMCs of tuberculosis (TB) patients and healthy controls, and there were still almost 4000 differentially methylated regions following completion of anti-TB treatment, and the majority of the affected genes were associated with the autophagy pathway [37,38]. Similarly, a distinct DNA methylation profile, which was enriched in the pentose phosphate pathway, T cell migration and IFN-γ production pathways, was uncovered in alveolar macrophages (AMs) after M. tuberculosis infection [39].…”
Section: Epigenetic Reprogrammingmentioning
confidence: 99%